Deskripsi Psikologis Atlet Remaja Berdasarkan Analisis Struktur EPPS - Listyo Yuwanto; Nadia Sutanto (Jurnal Ilmiah Psikologi MIND SET, 2012)
Adolescent athletes have a description of the psychological condition according to the characteristics of adolescent development. Adolescent athletes need psychological assistance to optimize performance. The aim of this research to describe the psychological characteristics of adolescents athletes at the Sports School X. The results are used to design a psychological support program for adolescent athletes. Subjects were 61 athletes from X sports school. Data were collected through the Edwards Personal Preference Schedule (EPPS). There are three groups of adolescent athletes based on research results. The first and third groups have a deficiency in aspects of personality. Psychological assistance programs that may be suggested: 1) development of personality, 2) emotional maturity, and 3) self-adjustment. The results are discussed further.